Role of Competency-Based Training Program by Sidoarjo Manpower Office in Improving Human Resources and Income: Peran Program Pelatihan Berbasis Kompetensi oleh Dinas Tenaga Kerja Sidoarjo dalam Meningkatkan Sumber Daya Manusia dan Pendapatan - Nisa' Nur Khofifah; Detak Prapanca (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Regional economic growth depends heavily on human resource quality and workforce adaptability. Specific Background High open unemployment in Sidoarjo Regency requires targeted skill-building strategies aligned with industrial needs. Knowledge Gap Existing studies rarely examine how competency-based training directly affects participant skill acquisition and community income in regional manufacturing. Aims This study analyzes the role of the shoe upper sewing training program by the Sidoarjo Manpower Office in enhancing human resources and local income. Results Triangulation reveals that practical training improves technical and soft skills while direct industry partnerships secure steady employment and higher wages for graduates. Novelty The research demonstrates a direct functional framework connecting municipal vocational training with immediate corporate workforce integration. Implications Competency-based initiatives effectively reduce regional open unemployment and foster sustainable local economic growth when backed by strategic private-sector alliances. Keywords: Competency-based Rraining, Human Resources, Community Income, Unemployment, Manpower OfficeKey Findings Highlights: Competency-based shoe upper sewing training significantly enhances both technical competencies and soft skills of job seekers. Direct collaboration between municipal agencies and industrial partners provides immediate labor market placement for program participants. Vocational skill acquisition directly transforms unemployed individuals into wage-earning workers, supporting regional economic sustainability.